SAT0258 Baseline MRI/CRP as Predictors of Response to Etanercept in the Management of Patients with Non-Radiographic Axial Spondyloarthritis. (9th June 2015) - Brown, M.A.; Bird, P.A.; Robinson, P.C.; Mease, P.; van den Bosch, F.; Surian, C.; Wiid, Z.; Jones, H.; Szumski, A.; Marshall, L.
Abstract : Background: Treatment with TNFα inhibitors has been shown to be effective in improving disease activity and functional capacity in patients with non-radiographic axial spondyloarthritis (nr-axSpA). Evidence indicates that clinical response to anti-TNFα agents tends to be enhanced in nr-axSpA patients with magnetic resonance imaging (MRI)-documented sacroiliac (SI) joint inflammation and elevated C-reactive protein (CRP). Objectives: To determine if MRI sacroiliitis positivity and/or elevated CRP at baseline are predictive or associated with changes in measures of disease activity following etanercept (ETN) treatment in patients with nr-axSpA. Methods: Patients with symptom duration >3 mths–<5 yrs, meeting ASAS axSpA classification criteria but not radiographic criteria for ankylosing spondylitis, having BASDAI ≥4, and failure with ≥2 NSAIDs were randomized to 12 wks of double-blind treatment with ETN 50mg QW or PBO. Both groups continued stable NSAID therapy. Standard clinical outcomes were assessed in 4 patient subgroups based on MRI sacroiliitis (positive/negative [+/-]) and CRP (elevated/normal [+/-]) status at baseline. MRI sacroiliitis positivity was defined as SPARCC SI joint score ≥2; elevated CRP was defined as >3 mg/L. Results: A total of 200 subjects (ETN, n=95; PBO, n=105) were included in these analyses. At baseline, breakdown according to MRI sacroiliitis and CRP status was: MRI-/CRP-, n=38; MRI+/CRP-, n=74; MRI-/CRP+, n=21; MRI+/CRP+, n=67. At Week 12, the primary endpoint of ASAS40 was achieved by more patients receiving ETN than those receiving PBO irrespective of MRI/CRP status at baseline (Table ). The greatest ASAS40 response was observed in patients with MRI+/CRP+ at baseline and the lowest response was seen in the MRI-/CRP- subgroup. Similar observations were made for all other clinical endpoints with a markedly higher proportion of MRI+/CRP+ patients achieving ASAS20, BASDAI50 and clinically important improvements (Δ≥1.1) in ASDAS-CRP/ESR than those in the other MRI/CRP subgroups. Conclusions: Our findings, in patients with early, active nr-axSpA and an inadequate response to ≥2 NSAIDs, are consistent with the hypothesis that a combination of MRI positivity and elevated hsCRP at baseline has a positive predictive value on the SI joint inflammation score and a better clinical response to ETN. A larger sample size is required to test this definitively. Disclosure of Interest: M. Brown Grant/research support from: Abbvie, Pfizer, UCB, Wyeth, Leo Pharma, NIAMS, NHMRC, Arthritis Australia, Qld Government, Consultant for: Pfizer, Abbvie, UCB, Speakers bureau: Pfizer, Abbvie, UCB, P. Bird Speakers bureau: Pfizer, Abbvie, Roche, Janssen, BMS, P. Robinson Grant/research support from: NHMRC, ARA, RACP, Consultant for: Pfizer, UCB, Abbvie, Janssen, Menarini, Speakers bureau: Menarini, Janssen, Abbvie, UCB, P. Mease Grant/research support from: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Crescendo, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Covagen, Crescendo, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Crescendo, Genentech, Janssen, Lilly, Pfizer, UCB, F. van den Bosch Consultant for: Abbvie, Celgene, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen, Novartis, Pfizer, UCB, C. Surian Employee of: Pfizer, Z. Wiid Employee of: Pfizer, H. Jones Employee of: Pfizer, A. Szumski Consultant for: Employee of inVentiv Health and was contracted by Pfizer Inc. to provide statistical support, L. Marshall Employee of: Pfizer